Preparation of active antibacterial LDPE surface through multistep physicochemical approach: I. Allylamine grafting, attachment of antibacterial agent and antibacterial activity assessment - Bílek, František; Křížová, Táňa; Lehocký, Marián (Colloids and surfaces. B, Biointerfaces, 2011)
Low-density polyethylene (LDPE) samples were treated in air plasma discharge, coated by polyallyamine brush thought copolymeric grafting surface-from reaction and deposited four common antibacterial agents (benzalkonium chloride, bronopol, chlorhexidine and triclosan) to gain material with active antibacterial properties. Surface characteristics were evaluated by static contact angle measurement with surface energy evaluation ATR-FTIR, X-ray Photoelectron Spectroscopy (XPS) and SEM analysis. Inhibition zone on agar was used as in vitro test of antibacterial properties on two representative gram positive Staphylococcus aureus (S. aureus) and gram negative Escherichia coli (E. coli) strains. It was confirmed, that after grafting of polyallyamine, more antibacterial agent is immobilized on the surface. The highest increase of antibacterial activity was observed by the sample containing triclosan. Samples covered by bronopol did not show significant antibacterial activity.
Keywords: Benzalkonium Compounds; polyethylen; triclosan; fotoelektronová spektroskopie; Polyethylene; spektroskopie infračervená s Fourierovou transformací; propylenglykoly; Triclosan; antibakteriální látky; Allylamine; molekulární struktura; Anti-Bacterial Agents; Microbial Sensitivity Tests; allylamin; Molecular Structure; mikrobiální testy citlivosti; Chlorhexidine; polyaminy; Propylene Glycols; Spectroscopy, Fourier Transform Infrared; benzalkoniové sloučeniny; Polyamines; chlorhexidin; Photoelectron Spectroscopy